The CROCO (CROhn's Disease COhort Study) - study design and protocol - Revés, Joana; Buisson, Anthony; Burisch, Johan; Arebi, Naila; Ungaro, Ryan; Vieujean, Sophie; Cravo, Marília; Ellul, Pierre; Duricova, Dana; Sebastian, Shaji; Rodríguez-Lago, Iago; Ordás, Ingrid; et al. (Therapeutic advances in gastroenterology, 2025)
BACKGROUND: Crohn's disease (CD) is a chronic, relapsing and remitting inflammatory bowel disease that can be associated with significant bowel damage and disability. The Lémann Index (LI) is a validated tool for measuring cumulative bowel damage in CD patients through a comprehensive assessment of stricturing, penetrating and surgical lesions. However, prospective studies evaluating bowel damage progression in recently diagnosed CD patients remain limited. OBJECTIVES: To characterise the absolute and longitudinal variations in bowel damage progression, as measured by the LI, in a cohort of recently diagnosed CD patients, and to assess its association with relevant disease features, including disease phenotype, treatment strategies, biomarkers and disability. DESIGN: Study protocol for the Crohn's Disease Cohort Study (CROCO Study), a multicentre, European, prospective cohort study. METHODS AND ANALYSIS: Patients with recently diagnosed CD (within the previous 12 months) will be enrolled and followed up for 5 years. Patients will receive standard-of-care treatment determined by the practising gastroenterologist. Morphological assessments to measure the LI and to evaluate bowel damage progression will be performed at years 1, 3 and 5 after the diagnosis. Disability will be assessed annually using the Inflammatory Bowel Disease - Disability Index (IBD-DI). The primary outcome will be the absolute LI at year 3 following diagnosis. Predictors of bowel damage progression and the association between bowel damage and disability will be analysed. DISCUSSION: The CROCO study represents a unique multicentre cohort of recently diagnosed CD patients, designed to advance the understanding of CD's natural history and evolution. It will facilitate the development of composite scores for predicting bowel damage progression and provide valuable tools for designing future disease-modification trials. TRIAL REGISTRATION: NCT05420233.
Keywords: Crohn’s disease; Lémann index; bowel damage; disability